1981
DOI: 10.2307/3898444
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Continuous and Rotational Grazing

Abstract: Continuous and rotational grazing of a brome-alfalfa-creeping red fescue pasture was compared at the University of Alberta Ranch in 1975, 1976, 1977, and 1978. Productivity, in terms of animal weight gain and dry-matter consumption, was studied together with changes in the sward composition. In 1977 and 1978 the weight gains from the rotationally grazed areas were nearly double those obtained from continuous grazing (218 vs 119 kg/ha). The percentage by weight of alfalfa in the sward increased under rotational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…A study in the United States found that rotational grazing, as compared with continuous grazing, increased beef gain per unit area by 35-61 percent and the profit from milk by 61 percent (Henning et al 2000). Walton, Martinez, and Bailey (1981) also found a 63.5 percent weight gain of cows due to rotational grazing. To obtain a conservative estimate, we assumed that overgrazing reduces carcass live weight and milk production by 32 percent.…”
Section: Nigermentioning
confidence: 81%
“…A study in the United States found that rotational grazing, as compared with continuous grazing, increased beef gain per unit area by 35-61 percent and the profit from milk by 61 percent (Henning et al 2000). Walton, Martinez, and Bailey (1981) also found a 63.5 percent weight gain of cows due to rotational grazing. To obtain a conservative estimate, we assumed that overgrazing reduces carcass live weight and milk production by 32 percent.…”
Section: Nigermentioning
confidence: 81%
“…Rotational stocking is generally accepted as essential to maintain alfalfa stands and to allow vigorous regrowth and subsequent animal productivity (Leach 1979;Walton et al 1981). The more intensive management required for rotational stocking systems is acceptable to dairy producers.…”
Section: Grazing Terms and Animal Typesmentioning
confidence: 99%
“…The effects of grazing system, forage maturity associated with advancing season, and forage species on the nutrition of grazing cattle have been evaluated (Walton et al 1981;Howarth and Goplen 1983;Sharrow 1983;Jung et al 1985;Sanderson and Wedin 1989;Beauchemin 1991;Beauchemin and Iwaasa 1993), but never in a single study. For example, Beauchemin (1991) reported decreases in CP (19.4 to 16.7%) and increases in NDF (38.8 to 47.6%) as alfalfa was harvested in early versus midbloom stages.…”
mentioning
confidence: 99%